Agent-based financial markets and New Keynesian macroeconomics: A synthesis - Matthias Lengnick; Hans-Werner Wohltmann (Kiel University, Department of Economics, 2011)
We combine a simple agent-based model of financial markets and a New Keynesian macroeconomic model with bounded rationality via two straightforward channels. The result is a macroeconomic model that allows for the endogenous development of business cycles and stock price bubbles. We show that market sentiments exert important influence on the macroeconomy. They introduce high volatility into impulse-response functions of macroeconomic variables and thus make the effect of a given shock hard to predict. We also analyze the impact of different financial transaction taxes (FTT, FAT, progressive FAT) and find that such taxes can be used to stabilize the economy and raise funds from the financial sector as a contribution to the costs produced by the recent crisis. Our results suggest that the FTT leads to higher tax revenues and better stabilization results then the FAT. However, the FTT might also create huge distortion if set too high, a threat which the FAT does not imply.
Keywords: E0; E62; G01; G18; 330; Agent-based modeling; stock market; New Keynesian macroeconomics; financial transaction tax; financial activities tax